Kredyty walutowe a limitowanie odsetek - skuteczność regulacji - Ganczar, Małgorzata (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
The main aim of this article is to analyze the efficiency of limitation interest regulation with particular reference to foreign currency loans. The article contains considering on consumer rights in this area. The paper is comparing models of limiting interest appearing in other European countries and in the world, as well as characterize of the phenomenon of limiting the usury were described. The article is aimed at an evaluation whether accepted regulations in the sufficing way are protecting the consumer, showing possible problems and other solutions which will enhance the position of the consumer on the market of financial services
Keywords: lichwa; konsumenci; kredyty walutowe; odsetki